Applied Servant Leadership: A Practical Approach - Christopher Jochum (Academic Chairpersons Conference Proceedings, 2023)
Leadership is a people business that requires courage, character and vulnerability. This workshop enables participants to explore the facets of servant leadership by developing their own personal mission statement, learning how to effectively address conflict, and understanding the value of building relationships with students, faculty and staff.
Keywords: Servant leadership; conflict resolution; relationships; mission statement development